Primary Cutaneous CD 30+ Anaplastic Large Cell Lymphoma. A Case Report and Literature Review - Miguel Ángel Serra Valdés; Julian Manzur Katrib; Yordanka Aleaga Hernández (Universidad de las Ciencias Médicas de Cienfuegos, 2014)
Primary cutaneous CD 30+ anaplastic large cell lymphoma is part of the spectrum of primary cutaneous CD30 + lymphoproliferative disorders, together with lymphomatoid papulosis. Its frequency is less than 0.5 x 100 000 inhabitants per year. It accounts for a very small proportion of non-Hodgkins lymphomas. The case of an 80-year-old female patient whose diagnosis was established in 2006 because of lesions on the face and neck is presented. The lesions continued to grow in an exaggerated fashion lately leading to deformity of her face. She was admitted due to neurological manifestations unrelated to the lesions. The presentation of this case is necessary because it requires performing differential diagnosis in clinical practice. Given its rarity, it is of interest to the medical community, especially trainees.